A facile rheological approach for the evaluation of "super toughness point" of compatibilized HDPE / MWCNT nanocomposites. (January 2020) - Wang, Yifei; Lv, Fucheng; Song, Yao; Yang, Yanyu; Cao, Yanxia; Wang, Jianfeng; Li, Chenlin; Wang, Wanjie
Abstract: Fast and efficient determination of the optimal mechanical property of a polymer/CNT nanocomposite is crucial to develop polymer conductive nanocomposites. This work establishes a rheological approach to evaluate the super-toughness point of compatibilized high density polyethylene (HDPE)/multi-walled carbon nanotube (MWCNT) nanocomposites. Results illustrate that three types of HDPE/MWCNT nanocomposites exhibit obvious gel plateaus in the dynamic rheological curves and the gel points of nanocomposites with compatibilizer shift to the low MWCNTs loading. The super-toughness points of HDPE/MWCNT nanocomposites with compatibilizers show the correspondence with the gel points acquired from the rheological data, indicating that dynamic rheology is an effective way to determine the super-toughness points of HDPE/MWCNT nanocomposites with compatibilizers. Furthermore, unique network structure at the gel points is directly observed and the new mechanism of toughness is proposed. This study provides new insights for effective control of the structures and properties of polymer/CNT nanocomposites. Highlights: A gel plateau was found in the dynamic rheological curve of HDPE/MWCNT nanocomposites. The super toughness points are corresponding to the gel points of compatibilized HDPE/MWCNT. Unique network structure at the gel point is directly observed. The new mechanism of super toughness at the gel point is proposed.